Determinan Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Ende - Awaludin, Abdurahman; Afifudin, Afifudin; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
Taxes are the main pillar in maintaining a country's financial stability by supporting government spending to meet the needs of the people. However, significant fluctuations in tax revenues, such as those observed in the Indonesian APBN, pose serious challenges. Despite tax revenues in the APBN averaging 78.6% over the last five years, government expenditure exceeds state revenues. This research aims to determine whether understanding of tax regulations, tax authorities' services, tax sanctions, and tax socialization influences individual taxpayer compliance. Sampling in this study was conducted using the Slovin formula. This research employs a quantitative method by directly distributing questionnaires to 100 individual taxpayers registered at KPP Pratama Ende. The research results indicate that tax authorities' services, tax sanctions, and tax socialization have a simultaneous effect on individual taxpayer compliance, while understanding tax regulations does not have a simultaneous effect on individual taxpayer compliance. It is expected that this research can be used as a consideration by relevant parties to improve understanding of tax regulations, services, sanctions, and socialization regarding individual taxpayer compliance.Keywords: Understanding tax regulations, fiscal services, tax sanctions, tax socialization, taxpayer compliance.